STUDY OF ENGLISH IDIOMS - Лукьянова, Юлия; Комарь, Вера (SWorldJournal, 2020)
The article is devoted to the study of phraseology of the English language and their use for better perception of the language in general. The authors highlight the importance of mastering phraseology, which contributes to their easier memorizing and use